Representasi Simbol Titi Gonggang di Pura Agung Gunung Raung Desa Taro, Kecamatan Tegallalang, Gianyar - Rahmat, Fauziana; Suwena, I Wayan (Humanis, 2017)
Hindus have many symbols, which relate to religious life, social life, and others. One form of symbols is a symbol of titi gonggang located in the Pura Agung Gunung Raung Taro Village. The existence of titi gonggang symbol in Pura Agung Gunung Raung has a strong relationship with Rsi Markandeya trip to Taro Village. Because titi gonggang is a specially made sign, to mark the arrival of Rsi Markandeya in the area. The aims of this research are to know: (a) how to form titi gonggang in Taro Village and (b) what is the meaning of titi gonggang symbol for Taro Village community. The symbolic form of titi gonggang located in several temples in Taro Village can be studied through representational theory, while the meaning of titi gonggang symbol according to Taro village community can be studied through interpretive theory. The concepts used as guidelines in this research are the concept of symbol representation, the concept of titi gonggang, the concept of Pura Agung Gunung Raung, and the concept of Taro Village community. The results showed that the shape of titi gonggang symbol in Puseh Puakan Temple, Pura Agung Gunung Raung, Puseh Tatag Temple, and Pura Dalem Tatag have in common. The physical shape is rectangular, with a hole. Above the hole, there is a bamboo that resembles a bridge called a titi. The type of bamboo used for titi is tiing rope or bamboo rope (Giganlochloa apus), while the length of bamboo can be measured using limbs, that is hand (depa). The measurement method is based on the kosala asta in the construction of the temple. Furthermore, socio-cultural significance is reflected in the community's treatment of titi gonggang as a mechanism for conflict resolution. In addition, the meaning of education was seen with people who apply character and courtesy in accordance with titi gonggang. The number of bamboo in titi gonggang in each of the temples with binary opposition, makes the diversity of symbolic meaning. One cause of the diversity of meaning is the spread of culture (diffusion).